Faktor-Faktor Yang Mempengaruhi Kebijakan Dividen - Aryanti Dirganingsih, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study aims to prove empirically the influence of profitability, liquidity, leverage, firm size and growth towards dividend policy in property, real estate and building construction company listed in Indonesian Exchange Stock (IDX) in 2016-2018. This study uses 23 company samples from 58 company data that were selected using purposive sampling technique. The results that obtained from this study are probability partially have a negative and significant effect towards dividend policy, liquidity partially have a positive and significant effect towards dividend policy, whereas leverage, firm size and growth partially doesn’t have a significant effect towards dividend policy.